Evaluate the Effect of Mirabilis Jalapa Linn. Seeds on Liver Function Tests of Healthy Rabbits (Medical Forum Monthly, 2023)
Objective: To observe the effect of Mirabilis Jalapa seeds on Liver function tests of Rabbit.Study Design: Experimental study.Place and Duration of Study: This study was carried out in the Department of Pharmacology and Therapeutics, Baqai Medical College/ University for a period of 2 months from 1.10.2011 to 30.11.2011.Materials and Methods: For this study twenty seven rabbits of either sex were selected and divided in three groups, control group, low dose group and high dose group, each group having nine rabbits. The dose of the drug was calculated according to weight of the animals.Results: The liver function tests (LFT) were done after 60 days administration of mirabilis jalapa seeds. Total serum bilirubin in control group was 0.69 ± 0.03, in low dose group 0.71 ± 0.03 and in high dose group 0.73 ± 0.03 with P value 0.197.Direct serum bilirubin was 0.34 ± 0.02; 0.34 ± 0.03; 0.31 ± 0.03 with P value 0.687 in control group, low dose group and in high dose group respectively. Indirect serum bilirubin was 0.35 ± 0.01 (control group); 0.37 ± 0.03 (low dose group) but in high dose group it decreased to 0.32 ± 0.02 with P value 0.409. SGPT in control group was 78.7 ± 3.01; in low dose group it was 74.1 ± 2.08 and in high dose it was 100.0 ± 2.08 with P value 0.001.Serum alkaline phosphate (IU/ L) was 44.4 ± 1.53 with low dose it was 26.1 ± 1.14 with high dose it was 114.6 ± 1.14 with P value 0.001.Conclusions: Mirabilis Jalapa seems to be useful drug and further studies regarding its use are recommended.